Cervical Length Distribution and Other Sonographic Ancillary Findings of Singleton Nulliparous Patients at Mid gestation - Costantine, Maged M. (Am J Obstet Gynecol, 2021)
BACKGROUND: Short cervix at mid-gestation, the presence of intra-amniotic debris, and cervical funneling are risk factors for preterm birth (PTB), however cervical length (CL) measurements and cutoffs are not well documented among pregnant patients of different gestational ages (GA) and self-reported races and ethnicities. OBJECTIVE: To describe the distribution of CL, and frequency of funneling and debris, at mid-gestation in nulliparous women by gestational age (GA) and race/ethnicity. STUDY DESIGN: Secondary analysis of screening data from a multicenter treatment trial of singleton nulliparous patients with short cervix, conducted at 14 geographically distribued, university affiliated medical centers in the U.S. Singleton nulliparous patients with no known risk factors for PTB were screened for trial participation and asked to undergo a transvaginal ultrasound to measure CL by a certified sonographer. The distribution of CL and the frequency of funneling and debris, were assessed for each GA week (16 to 22 weeks) and stratified by self-reported race and ethnicity, which for this study were catgorized as White, Black, Hispanic and other. Patients enrolled in the randomized trial were excluded from this analysis. RESULTS: 12,407 nulliparous patients were included in this analysis. The racial/ethnic distribution of study participants was as follows: White 41.6%, Black 29.6%, Hispanic 24.2%, and others 4.6%. The 10(th) percentile CL for the entire cohort was 31.1 mm, and when stratified by race and ethnicity, 31.9 mm for White, 30.2 mm for Black, 31.4 mm for Hispanic, and 31.2 mm for patients of other race and ethnicity (p<0.001). At each GA, the CL corresponding to tenth percentile was shorter in Black patients. The 25 mm value commonly used to define a short cervix, and thought to represent the 10(th) percentile, ranged from 1.3 to 5.4 percent across GA weeks and 1.0 to 3.8 percent across race and ethnicity groups. Black patients had the highest rate of funneling (2.6%), whereas Hispanic and Black patients had higher rates of intra-amniotic debris compared with White and other patients (p<0.001). CONCLUSIONS: Black patients had shorter CL and higher rates of debris and funneling compared with White patients. The racial and ethnic disparities in sonographic mid-trimester cervical findings may provide insight into the racial disparity in preterm birth rates in the US.